Rice Blast Control and Polyvarietal Planting in the Philippines: A Study in Genotype by Environment Biogeography - Falvo, Daniel J. (Social Science Diliman: A Philippine Journal of Society and Change; Vol 2 No 1 (2001), 2007)
Current approaches to biogeography are based on organismic biology. Certain biogeographical phenomena, however, cannot be fully understood using organismic approaches to biogeography. I employed an approach based on molecular biology and biochemistry that I call genotype by environment biogeography in order to provide a more complete understanding of why the dispersal of rice blast disease is less efficient in fields planted with mixtures of rice varieties. In a case study of an upland ricefield in the Philippines, I found that planting varietal mixtures results in a form of effective blast control that I call intrafield gene deployment. I suggest that intrafield gene deployment be used to design more effective methods of blast control in intensive rice agriculture.